Eficacia de la concialiación para resolver pretensiones sobre pensión de alimentos en el Centro de Concialiación del Ministerio de Justicia de Loreto - 2019 - Armas Torres, Piero Andre (2023)
The main objective of this investigation entitled, effectiveness of the conciliation to resolve claims on Alimony in the Center of Conciliation of the Ministry of Justice of Loreto - 2019, had as main objective to determine the effectiveness of the extrajudicial conciliation to solve the claims on pension of food at the Conciliation Center of the Ministry of Justice of Loreto. It was guided by the mixed approach, of a basic type with a simple descriptive design. The study population was made up of 60 people between personnel of the conciliation center of the Loreto Ministry of Justice and the conciliatory parties, having as a sample 100% of the total population, distributed as follows: 50% were the personnel of the conciliation center of the Loreto Ministry of Justice and the other 50% conciliatory parties. Likewise, it included as data collection techniques the survey, the semi-structured interview, direct observation and the analysis of conciliation records. As the most important result of the investigation, it was considered that the extrajudicial conciliation in the Conciliation Center of the Ministry of Justice, Loreto headquarters in 2019, to resolve the claims related to maintenance pensions, has high levels of effectiveness. Finally, this investigation concludes that the Conciliation Center of the Ministry of Justice of Loreto has promoted the effectiveness of the solution of the claims on the issue of alimony, since there is no active intervention of defense lawyers of the parties.